HERMENEUTIKA HUKUM ISLAM INKLUSIF DI INDONESIA - Moh Dahlan (Universitas Islam Negeri Fatmawati Sukarno, 2015)
The goal of this Islamic law study is to offer ijtihad hermeneutics of Islamic law which is able to bring the discourse of Islamic law inclusively by digging the spirit and essence of the Islamic law of the passages of the Koran and Sunnah, as well as the aspects of its implementation. The paradigm of Islamic law study used is philosophical hermeneutics of Hans George Gadamer. The study says that the study of philosophical hermeneutics of Islamic law has an important role in transforming the values of Islamic law into national law system. With a philosophical hermeneutics, the study of Islamic law will be able to realize the norms of Islamic law that is inclusive and dynamic in responding to the dynamics of the life of the people and the nation. The birth of a number of laws and local regulations that nuanced with Islamic law is not a barrier in building a good national legal order, but rather a real contribution in the effectiveness of the imposition of Islamic law in the legislation were valid and constitutional